2017
DOI: 10.22159/ijap.2017v9i6.22448
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Vesicles of Salbutamol Sulphate in Metered Dose Inhalers: Formulation, Characterization and in Vitro Evaluation

Abstract: Objective: The present work was aimed to prepare niosomes entrapping salbutamol sulphate (SS) using reversed phase evaporation method (REV).Methods: Niosomes were prepared by mixing span 60 and cholesterol in 1:1 molar ratio in chloroform, SS in water was then added to organic phase to form niosomal SS. Formulations after evaporation of chloroform, freeze centrifuged then lyophilized, were evaluated for particles size, polydispersity index (Pdi), zeta-potential, morphology, entrapment efficiency (EE%) and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…AT-PLGA-CS-NP morphology was inspected by transmission electron microscopy (TEM; H-600, Hitachi, Tokyo, Japan). 20,21 Entrapment Efficiency (EE) and Drug Loading of AT-PLGA-CN-NPs…”
Section: Preparation Of At-plga-cs-npsmentioning
confidence: 99%
See 1 more Smart Citation
“…AT-PLGA-CS-NP morphology was inspected by transmission electron microscopy (TEM; H-600, Hitachi, Tokyo, Japan). 20,21 Entrapment Efficiency (EE) and Drug Loading of AT-PLGA-CN-NPs…”
Section: Preparation Of At-plga-cs-npsmentioning
confidence: 99%
“…Zero-order, first-order, and Higuchi diffusion models of linear regression and the Korsmeyer-Peppas model were used to study the in vitro release of AT. 20 In vivo Anti-Inflammatory Assessment of AT-PLGA-CS-NP Thermosensitive Gels Albino rabbits (2-2.5 kg) were obtained from Egyptian farms and kept under standard laboratory conditions. All animal work was conducted in accordance with the guidelines for the care and use of laboratory animals and was approved by the ethical committee of faculty of pharmacy of the British University in Egypt.…”
Section: Kinetic Studymentioning
confidence: 99%
“…Dissolution test was performed on three Marizev® tablets by dissolution USP procedure using 900 ml of 0.1 N HCl. Mild agitation of 50 rpm was enough to study the release of the drug based on withdrawn aliquots at predetermined intervals for 60 min . Furthermore, 5 ml sample was withdrawn through a 0.45 μm syringe filter and replaced with 5 ml of 0.1 N HCl at 5, 10, 15, 20, 25, 30, 40, 50 and 60 min and then the procedure mentioned earlier was repeated for measuring the previously mentioned withdrawn 5 ml samples after dilution in 25 ml volumetric flasks using water.…”
Section: Methodsmentioning
confidence: 99%
“…Our results were in good agreement with Arafa et al, [2017] who found that the release profile of salbutamol sulphate from niosomes followed Higuchi model. This kinetic pattern indicated that the drug release was dominated by diffusion model which normally depended on drug concentration gradient between nano-vesicles and dissolution media with penetration of this media through a porous wall which accompanied by matrix disruption [21]. …”
Section: Entrapment Efficiency Of Itraconazole Proniosomesmentioning
confidence: 99%
“…This was due to the acyl-chain structure of span 60, which could affect cholesterol interactions causing variations in cholesterol distribution. The polar head group of non-ionic surfactant must cover the non-polar portion of cholesterol; this coverage is essential to avoid the unfavourable free energy of cholesterol that when contacts with water decrease the repulsion between cholesterol molecules [21].…”
Section: Optimization Of the Formulation Ingredientsmentioning
confidence: 99%